2018
DOI: 10.1002/prp2.436
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of Enasidenib following single oral doses in Japanese and Caucasian subjects

Abstract: The aim of this study was to assess and compare the pharmacokinetics (PK) and safety of Enasidenib in healthy adult male Japanese subjects to healthy adult male Caucasian subjects. This was a phase 1, single dose study to evaluate the PK and safety of Enasidenib in healthy adult male Japanese subjects relative to healthy adult male Caucasian subjects. A total of 62 subjects (31 Japanese and 31 Caucasian) were enrolled into three dose cohorts (single doses of 50 mg, 100 mg, or 300 mg Enasidenib). Blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The % remained was 94.7 and 74.4 in mice liver microsomes and 97.6 and 80.7 in human liver microsomes, for enasidenib and AGI-16903, respectively at the end of 30 min incubation time. These results clearly indicate that the percent remained for enasidenib was higher than AGI-16903 in both matrices and support for the higher exposure for enasidenib in mice (present study) and in humans as reported by Li et al [8].…”
Section: Pharmacokinetic Studysupporting
confidence: 92%
See 3 more Smart Citations
“…The % remained was 94.7 and 74.4 in mice liver microsomes and 97.6 and 80.7 in human liver microsomes, for enasidenib and AGI-16903, respectively at the end of 30 min incubation time. These results clearly indicate that the percent remained for enasidenib was higher than AGI-16903 in both matrices and support for the higher exposure for enasidenib in mice (present study) and in humans as reported by Li et al [8].…”
Section: Pharmacokinetic Studysupporting
confidence: 92%
“…We have also digitalized using DigitizeIt (version 2.0.0; accessed on 27 July 2019 available at https://www.digitizeit.de) the reported plots of enasidenib and AGI-16903 in healthy Caucasian and Japanese subjects post administration 100 mg oral dose of enasidenib [8] and found that enasidenib and AGI-16903 reaches the reported LLOQ (1.01 ng/mL) by 14 th and 10 th day, respectively which is contrary to the reported (up to 28 th day). This indicates that the method used by Li et al [8] for quantitation of enasidenib and AGI-16903 may not be sensitive enough to determine the plasma concentrations of enasidenib and AGI-16903 till the reported time despite using higher volume of plasma (100 µL).…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Now, enasidenib has provided a new treatment approach for patients with refractory AML with recurrence and IDH2 mutations [11][12][13]. However, there are only three papers which reported the pharmacokinetic profiles of enasidenib [14][15][16][17]. Among them, only one LC-MS/MS method has been published to determine the concentration of enasidenib in biological media in detail, which has long analytical time, low sensitivity, and complex sample preparation process [16].…”
Section: Introductionmentioning
confidence: 99%